The Effect of Using Methods in Teaching the Own Layer Module of the Uzbek Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article talks about conducting classes on the basis of modern pedagogical methods and the positive results of these methods in students' mastery of subjects. The main rules of the methods, the purpose of their implementation, the procedure for implementing the methods are covered based on questions and tasks.